Pojęcie przekładu w Indiach: Zarys problematyki (Między Oryginałem a Przekładem, 2022)
THE CONCEPT OF TRANSLATION IN INDIA: AN OVERVIEWThis study aims to outline the most relevant contemporary critical remarks concerning the concept of translation and the presence of translational reflection in India, aiming to fill the gap perceived in Polish translatology.